Role of governance, ethics and integrity in managing information technology resources: Muslim practitioner’s view - Ahlan, Abdul Rahman; Ajayi, Binyamin; Hussin, Husnayati (2013)
No doubt there is established best practices and frameworks guiding the proper usage of Information Technology (IT) resources in achieving optimality. However, what is obtainable today in the Muslims world where ethics and integrity are essential fundamentals of faith gives more than meet the eyes. This study explored the ITG research, issue of ethics and learning from interview sessions held with a Muslim IT Practitioner practicing in an educational environment it viewed the current state of the Muslims in the optimal use of the IT resources. It sees IT Governance (ITG) as control exercised by the board of directors and managements in the formulation of right decisions. It was observed that while these frameworks have nothing alien to Islam, the Muslims who are supposed to be the harbingers of its ideals are rarely seen as been up and doing. The Ummah needs to look inward to internalise the best practices enabled in IT by putting it to work. Thus, they will be optimal in their ways and end up doing acts of worship in accordance with the letter and spirit of their faith.